2020
DOI: 10.1101/2020.07.20.20147769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Outcomes With the Use of Prophylactic Versus Therapeutic Anticoagulation in COVID-19

Abstract: Background: This study is the first of its kind to assess the impact of preemptive therapeutic dose anticoagulation on mortality compared to prophylactic anticoagulation among COVID-19 patients. Its findings provide insight to clinicians regarding the management of COVID-19, particularly with the known prothrombotic state. Research Question: To determine the impact of anticoagulation on in-hospital mortality among COVID-19 positive patients with the a priori hypothesis that there would be a lower risk of in-ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…While reduced VTE events and mortality has been noted with full-dose anticoagulation compared to low-dose, 3,7 more recent studies have found either no benefit between prophylactic and therapeutic anticoagulation or have found that in-hospital mortality was 2.3 times greater with preemptive treatment-dose anticoagulation from the time of hospital admission. 8,9 With limited data in large populations of hospitalized COVID-19 patients to date, as well as conflicting data on predictors of VTE or mortality, we assessed the prevalence and predictors of VTE or mortality in hospitalized COVID-19 patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While reduced VTE events and mortality has been noted with full-dose anticoagulation compared to low-dose, 3,7 more recent studies have found either no benefit between prophylactic and therapeutic anticoagulation or have found that in-hospital mortality was 2.3 times greater with preemptive treatment-dose anticoagulation from the time of hospital admission. 8,9 With limited data in large populations of hospitalized COVID-19 patients to date, as well as conflicting data on predictors of VTE or mortality, we assessed the prevalence and predictors of VTE or mortality in hospitalized COVID-19 patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Since elevated D-dimer levels are often found in patients with clotting problems, severe COVID-19 patients with elevated D-dimer levels are treated with unfractionated heparin or LMWH as an anticoagulation to reduce mortality ( Table 1 ) [ 82 , 83 , 84 , 85 , 86 , 87 ]. However, the current anticoagulation options have limited effect on thrombosis in general COVID-19 patients, and some of the observed effects were not significant [ 88 , 89 , 90 , 91 ]. In a Dutch study of COVID-19 patients, all 184 ICU patients received at least standard doses thromboprophylaxis, but thrombosis still occured in 31% patients, including 27% venous thromboembolism (VTE) and 3.7% arterial thrombotic events [ 92 ].…”
Section: Coagulation Dysfnction In Covid-19 and The Risk Of Hitmentioning
confidence: 99%
“…30 However, more recent studies have found either no benefit between prophylactic and therapeutic anticoagulation or have found that in-hospital mortality was 2.3 times greater with preemptive treatment-dose anticoagulation from the time of hospital admission. 15,31 Lastly, whether the mechanisms of thrombosis in COVID-19 are due primarily to in situ immunothrombosis or classic thromboembolic macrovessel disease continues to be a matter of debate, with the former theoretically less susceptible and more resistant to heparin-based strategies for management, even with escalating or treatment doses. 32 In short, there continues to remain true clinical equipoise for both the efficacy and safety of using treatment-dose anticoagulation for primary thromboprophylaxis in this high-risk hospitalized COVID-19 population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent small randomized trial of therapeutic versus prophylactic anticoagulation in patients with severe COVID-19 revealed that therapeutic anticoagulation improved ventilator-free days (30). However, more recent studies have found either no benefit between prophylactic and therapeutic anticoagulation or have found that in-hospital mortality was 2.3 times greater with preemptive treatment-dose anticoagulation from the time of hospital admission (15,31). Lastly, whether the mechanisms of thrombosis in COVID-19 are due primarily to in situ immunothrombosis or classic thromboembolic macrovessel disease continues to be a matter of debate, with the former theoretically less susceptible and more resistant to heparin-based strategies…”
Section: Accepted Manuscriptmentioning
confidence: 99%